2017
DOI: 10.1007/s12519-017-0003-z
|View full text |Cite
|
Sign up to set email alerts
|

Newborn screening for remethylation disorders and vitamin B12 deficiency-evaluation of new strategies in cohorts from Qatar and Germany

Abstract: The proposed strategy for samples from Qatar allows inclusion of remethylation disorders and vitamin B deficiency in the screening panel, while lowering the recall rate. An adapted second-tier strategy is presented for screening in Germany and will be prospectively evaluated over the next years in a pilot project named "Newborn Screening 2020".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 17 publications
1
44
0
1
Order By: Relevance
“…Gramer et al have proposed an algorithm to detect CBSD and RMD with tHcy as a second‐tier test in all newborns with abnormalities in either Met (lower cut‐off only) or Met/Phe (lower and upper cut‐offs) or elevated C3 or C3/C2. This approach was tested in a single centre and did not only identify patients from the local population but also patients documented in the Region 4 Collaborative Project . The authors show that second‐tier measurement of tHcy allows adjusting the decision limits of the primary markers towards the median, which results in a smaller proportion of undetected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Gramer et al have proposed an algorithm to detect CBSD and RMD with tHcy as a second‐tier test in all newborns with abnormalities in either Met (lower cut‐off only) or Met/Phe (lower and upper cut‐offs) or elevated C3 or C3/C2. This approach was tested in a single centre and did not only identify patients from the local population but also patients documented in the Region 4 Collaborative Project . The authors show that second‐tier measurement of tHcy allows adjusting the decision limits of the primary markers towards the median, which results in a smaller proportion of undetected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is some evidence that the C3 to C2 ratio and/or C3 to C16 ratio together with C3 are better than C3 level alone for detecting or identifying the babies with nutritional B12 deficiency [7] , [8] , [17] . Some authors have also suggested to measure tHcy from first DBS and if it is elevated, then evaluate the second-tier markers like methionine (Met), Met to phenylalanine ratio, C3 and C3/C2, which is considered to be valuable method to detect remethylation disorders and vitamin B12 deficiency [18] . The MMA, measured from DBS as a secondary test, might also add value to increase sensitivity and specificity in detection of vitamin B12 deficiency [8] .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, not all Cobalamin C and D deficiency can be identified by newborn screening using approaches based solely on elevated C3 [ 22 ]. Depending on the quality of data describing the confirmatory work-up, “MMA” cases without definite report of the final diagnosis might also include some cases with severe maternal vitamin B 12 deficiency, which can sometimes also be picked up by elevated C3 on newborn screening [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%